Psychological status is associated with health related quality of life in patients with rheumatoid arthritis - Nas, Kemal; Sarac, Aysegul Jale; Gur, Ali; Cevik, Remzi; Altay, Zuhal; Erdal, Akin; Ozgocmen, Salih (Ios Press, 2011)
Objective: Rheumatoid arthritis (RA) is a chronic and disabling disease frequently effects physical and psychological well being. The aim of the present study was to determine the impact of psychological status on health related quality of life in patients with RA and also to assess which quality of life (QoL) instrument - disease specific and generic - is more prone to this effect. Methods: A total of 421 patients with RA recruited from joint database of five tertiary centers. Depression and anxiety risks were assessed by the Hospital Anxiety and Depression Scale (HADS); and quality of life assessed by Rheumatoid Arthritis Quality of Life (RAQoL), Nottingham Health Profile (NHP) and The Short Form 36 (SF 36) questionnaire. Results: Patients with higher risk for depression or anxiety had poorer quality of life compared to the patients without risk for depression or anxiety. Depression and anxiety scores significantly correlated with quality of life questionnaires. There was significant association between anxiety and depression with worsening in both disease specific and generic health related quality of life. However, RAQoL showed more association with depression and anxiety levels. Conclusion: Higher depression and anxiety risks showed increased deterioration in quality of life. Compared to generic QoL scales, RAQoL scale, a disease specific QoL instrument, is much more influenced by depression and anxiety.
Keywords: Rheumatoid arthritis; depression; anxiety; quality of life